THE ANALYSIS OF TREATMENT QUALITY OF TEMPORARY TEETH AT CHILDREN OF POLTAVA REGION IN 2005-2014 - Шешукова, О.В. (World of Medicine and Biology, 2015)
The article analyzes the quality of treatment of temporary teeth in children, Poltava region in the last decade. With the help of indicators proposed by the author defined the growth of complications of caries of deciduous teeth, indicating a decrease in the effectiveness of primary prevention of tooth decay, and imperfections of rehabilitation. It outlines the problems in the organization of therapeutic and preventive work in children's dental service and solutions.
Keywords: complicated caries; temporary teeth; the quality of treatment